Language Learning Strategies Used by English Department Students of English at STKIP PGRI Banjarmasin - Hidya Maulida; Yasyir Fahmi Mubaraq (Universitas Muhammadiyah Kalimantan Timur, 2023)
Speaking skill is one of skill has to master by English language students. In the speaking IV course, students train to speak English through practice public speech, seminar and debate also when the students present in front of the other student in learning process. The fluency of speaking skill is also supported by leaning strategies. The objective of this research was to describe learning strategies used by the eighth semester students as fluent speaker of English department at STKIP PGRI Banjarmasin. The data were processed and analysis based on the procedures that was chosen to find the strategies that used by the students as fluent speakers. Instruments for this research were questionnaire and interview. The result of this research revealed that the eighth semester students who are categorized as fluent speaker used all language learning strategies, the most frequently strategy used by students as fluent speakers was cognitive strategies and the least frequently strategy used by students as fluent speakers was social strategies.